دور الأعضاء المستقلين في مجالس الإدارة - شاوشي، كهينة (جامعة الوادي University of Eloued, 2025)
هدفت الدراسة إلى التعرف على دور الأعضاء المستقلون في دعم مجلس الإدارة وتمكينه من أداء مهامه بكفاءة وفعالية. من خلال عرض الجوانب النظرية المتعلقة بالموضوع، إضافة إلى استعراض تجربة الجزائر في هذا المجال، من خلال تعيين أعضاء مستقلين في مجالس إدارة البنوك العمومية ابتداءً من عام 2021. أظهرت نتائج الدراسة أن الأعضاء المستقلين يشكلون عنصرًا أساسيًا في هيكلة مجالس الإدارة، حيث يُتوقع أن يُسهم تعيينهم في البنوك العمومية الجزائرية في تقديم رأي محايدة حول التوجهات الاستراتيجية، وتعزيز تحقيق أهدافها، إلى جانب الإشراف الفعّال على الأداء العام للبنك. ومع ذلك، تواجه هذه العملية جملة من التحديات التي قد تُحدّ من فعاليتها، أبرزها قلة تمثيل الأعضاء المستقلين في المجالس، إضافة الجمع بين منصب رئيس مجلس الإدارة والمدير التنفيذي في البنوك العمومية الجزائرية The study aimed to underscore the critical role of independent board members in strengthening the effectiveness of boards of directors and enhancing their ability to fulfill their responsibilities. It explores the theoretical foundations of the subject and examines Algeria’s recent experience, particularly the appointment of independent members to the boards of public banks beginning in 2021. The findings showed that independent members are a vital part of the structure of boards of directors. Their appointment in Algerian public banks is expected to contribute to offering objective insights into strategic directions and to enhancing effective oversight of the bank's overall performance. However, their impact is limited by their low representation and the common practice of combining the roles of board chairman and CEO.
The Role of Independent Board Members: A Study of the Reality of Public Banks in Algeria
مقال
Keywords: حوكمة; مجلس الإدارة; الاستقلالية; أعضاء مستقلين; لبنوك العمومية الجزائرية; Governance; board of directors; independence; independent members